Sexuality in a community based sample of adults with autism spectrum disorder - Gilmour, Laura; Schalomon, Melike; Smith, Veronica (My University, 2011)
Few studies have examined the sexual attitudes and behaviours of individuals with high functioning autism spectrum disorders (ASDs) living in community settings. A total of 82 (55 female and 17 male) adults with autism were contrasted with 282 members of the general population on their responses to an online survey of sexual knowledge and experiences. Findings revealed that individuals with ASD display an interest in sex and engage in sexual behaviours and showed no significant differences in breadth and strength of sexual behaviours and comprehension of sexual language when contrasted with non-ASD participants. However, despite these similarities, a higher rate of asexuality was found among individuals with ASD. In addition, the results of the current study indicated that females with ASD show a significantly lower degree of heterosexuality when compared to males with ASD. The results also suggested a higher degree of homosexuality among females with ASD although this effect did not reach significance.
Keywords: autism spectrum disorder; sexual behaviour; sexual orientation